Spectral response of 4 vegetation types during 2009-2010 occurrence of moderate El Nino Southern oscillation in Cagayan river basin - Montoya, Cristina M. (Sylvatrop, 2017)
An usual warming of sea surface temperature (SST) along the equatorial Pacific was established in June 2009 to June 2010 which developed weak to moderate El Nino Southern Oscillation (ENSO). Time series vegetation indices of 4 vegetative covers derived from Moderate Resolution Imaging Spectroaradiometer (MODIS) sensors were used to understand the effects of El Niño in Cagayan River Basin. The research process used in this study can serve as a guide for vegetation assessment and monitoring, particularly during an El Niño event, for timely crop assessment and monitoring.